Chemical characterisation and hepatoprotective potential of Cosmos sulphureus Cav. and Cosmos bipinnatus Cav. Issue 6 (19th March 2019) - Saleem, Mohammad; Ali, Hafiz Akbar; Akhtar, Muhammad Furqan; Saleem, Uzma; Saleem, Ammara; Irshad, Iram
Abstract: This study was conducted to validate the hepatoprotective activity of Cosmos sulphureus and Cosmos bipinnatus . Aqua-methanolic extracts of both plants were evaluated for the presence of various phyto-constituents through HPLC. Different doses of both plant extracts were administered to rats for nine days. Standard control was silymarin 100 mg/kg. Paracetamol 1 gm/kg was administered 3 h post treatment on 9th day for induction of hepatotoxicity. Blood was collected for the evaluation of liver biochemical markers and livers were removed for histopathological evaluation 24 h post-paracetamol treatment. HPLC analysis revealed the presence of quercetin, gallic acid, caffeic acid and chlorogenic acid in both plant extracts. The extracts of both plants decreased the level of alanine aminotransaminase and total bilirubin significantly ( p  < 0.05), dose dependently and protected hepatocytes from paracetamol-induced hepatotoxicity. It can be concluded that both plants may possess hepatoprotective activity possibly due to the presence of quercetin and phenolic compounds. Abstract :